The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/app10051633
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Natural Convection Flow in a Square Porous Enclosure Filled with a Micropolar Nanofluid under Magnetohydrodynamic Conditions

Abstract: The laminar, natural convective flow of a micropolar nanofluid in the presence of a magnetic field in a square porous enclosure was studied. The micropolar nanofluid is considered to be an electrically conductive fluid. The governing equations of the flow problem are the conservation of mass, energy, and linear momentum, as well as the angular momentum and the induction equations. In the proposed model, the Darcy–Brinkman momentum equations with buoyancy and advective inertia are used. Experimentally obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
0
4
0
1
Order By: Relevance
“…The results of Afrand et al [126] demonstrated that the heat transfer rate increase with the Rayleigh number and decreases with the Hartmann number. Karagiannakis et al [127] found that the magnetic field hindered the movement of nanofluids, and thus significantly reduced the local Nusselt number owing to the inhibition of convection by magnetic fields, in which excessive nanoparticle volume fraction also can worsen heat transfer by hindering the flow of nanofluids [128]. Tran et al [129] carried out a thermal analysis of ferrofluid under buoyancy and external force and found that the thermal plume and the average Nusselt number both decrease with the Hartmann number.…”
Section: Negative Effectmentioning
confidence: 99%
“…The results of Afrand et al [126] demonstrated that the heat transfer rate increase with the Rayleigh number and decreases with the Hartmann number. Karagiannakis et al [127] found that the magnetic field hindered the movement of nanofluids, and thus significantly reduced the local Nusselt number owing to the inhibition of convection by magnetic fields, in which excessive nanoparticle volume fraction also can worsen heat transfer by hindering the flow of nanofluids [128]. Tran et al [129] carried out a thermal analysis of ferrofluid under buoyancy and external force and found that the thermal plume and the average Nusselt number both decrease with the Hartmann number.…”
Section: Negative Effectmentioning
confidence: 99%
“…They are found the average Nusselt number is obtained in polynomial in the presence of obstacles. Transient, laminar flow and natural convection of a micropolar‐nanofluid (Al 2 O 3 /water) in the presence of a magnetic field have been addressed by Bourantas et al 26 The authors in Reference [27] studied the laminar and natural convective flow of a micropolar nanofluid in the presence of a magnetic field in a square porous enclosure. Authors in Reference [28] examined mixed convection through an isosceles triangular cavity enclosing micropolar nanofluid when a uniform magnetic field is applied along the x ‐axis.…”
Section: Introductionmentioning
confidence: 99%
“…They considered the effects of magnetism and its inclination angle on flow patterns. In another study, free convection flow in a square porous cavity saturated with micropolar NF under the magnetic influence was investigated by Karagiannakis et al 42 using a meshless collocation method; aiming to analyze the magnetohydrodynamic effect on flow properties. Sajjadi et al 17 considered sinusoidal boundary temperature distribution effect on natural convection of Cu–H 2 O in a porous enclosure using double multiple‐relaxation‐time (DMRT) LBM collision.…”
Section: Introductionmentioning
confidence: 99%